2015
DOI: 10.1007/s12010-015-1725-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Coated Microcrystals from Candida rugosa Lipase: Its Immobilization, Characterization, and Application in Resolution of Racemic Ibuprofen

Abstract: In this study, an economical heterogeneous biocatalyst, protein-coated microcrystals (PCMCs), was prepared from a commercial Candida rugosa lipase (CRL) and used for catalyzing esterification of (R, S)-ibuprofen enantiomers with isooctanol in isooctane. The main variables controlling the process (precipitating solvents, pH, saturated K2SO4 solution, and water content) were optimized via single-factorial experiments. Under optimum conditions, the enantiomeric excess of active S(+)-ibuprofen and total conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Previous studies indicated that the second derivative FT-IR spectra in the amide I region of an enzyme was used as a particularly sensitive probe of protein conformation 19 20 21 . To date, there have also been some reports on the use of the second derivative FT-IR spectra to study the conformational changes of an enzyme after immobilization 22 23 24 25 . Therefore, it was of great interest to comparatively investigate the secondary structure contents of PCL and PCL@MCNC and their conformational changes using FT-IR spectra to get some insight of the stabilization mechanism of the immobilized enzyme PCL@MCNC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that the second derivative FT-IR spectra in the amide I region of an enzyme was used as a particularly sensitive probe of protein conformation 19 20 21 . To date, there have also been some reports on the use of the second derivative FT-IR spectra to study the conformational changes of an enzyme after immobilization 22 23 24 25 . Therefore, it was of great interest to comparatively investigate the secondary structure contents of PCL and PCL@MCNC and their conformational changes using FT-IR spectra to get some insight of the stabilization mechanism of the immobilized enzyme PCL@MCNC.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Kim and co‐workers reported the accomplishment of lipase activation through lyophilization with ionic liquids or ionic surfactants [45–48]. Koo and co‐workers also reported efficient activation of lipase through lyophilizaton of ionic liquid type sol‐gel silica [49]; similar activation methods have been demonstrated by several groups [50–57].…”
Section: Introductionmentioning
confidence: 79%
“…After optimization, a yield of 80% in 1 h was obtained, clearly surpassing the results obtained with the commercial Lipozyme RM-IL [136]. In another contribution, lipase from Candida rugosa was used to produce PCMCs [137]. The preparation of the biocatalysts was optimized via single-factorial experiments (the studied variables were precipitating solvents, pH, saturated K 2 SO 4 solution, and water content).…”
Section: Immobilization Of Enzyme By Protein-coated Microcrystals (Pcmentioning
confidence: 91%